Contribution of vascular resident mesenchymal stromal cells to abdominal aortic aneurysm pathogenesis: increased MMP-9 expression and ineffective immunomodulation - Ciavarella, Carmen <1986> (Alma Mater Studiorum - Università di Bologna, 2015)
Background. Ageing and inflammation are critical for the occurrence of aortic diseases. Extensive inflammatory infiltrate and excessive ECM proteloysis, mediated by MMPs, are typical features of abdominal aortic aneurysm (AAA). Mesenchymal Stromal Cells (MSCs) have been detected within the vascular wall and represent attractive candidates for regenerative medicine, in virtue of mesodermal lineage differentiation and immunomodulatory activity. Meanwhile, many works have underlined an impaired MSC behaviour under pathological conditions. This study was aimed to define a potential role of vascular MSCs to AAA development. Methods. Aortic tissues were collected from AAA patients and healthy donors. Our analysis was organized on three levels: 1) histology of AAA wall; 2) detection of MSCs and evaluation of MMP-9 expression on AAA tissue; 3) MSC isolation from AAA wall and characterization for mesenchymal/stemness markers, MMP-2, MMP-9, TIMP-1, TIMP-2 and EMMPRIN. AAA-MSCs were tested for immunomodulation, when cultured together with activated peripheral blood mononuclear cells (PBMCs). In addition, a co-colture of both healthy and AAA MSCs was assessed and afterwards MMP-2/9 mRNA levels were analyzed. Results. AAA-MSCs showed basic mesenchymal properties: fibroblastic shape, MSC antigens, stemness genes. MMP-9 mRNA, protein and enzymatic activity were significantly increased in AAA-MSCs. Moreover, AAA-MSCs displayed a weak immunosuppressive activity, as shown by PBMC ongoing along cell cycle. MMP-9 was shown to be modulated at the transcriptional level through the direct contact as well as the paracrine action of healthy MSCs. Discussion. Vascular injury did not affect the MSC basic phenotype, but altered their function, a increased MMP-9 expression and ineffective immunmodulation. These data suggest that vascular MSCs can contribute to aortic disease. In this view, the study of key processes to restore MSC immunomodulation could be relevant to find a pharmacological approach for monitoring the aneurysm progression.